Identification on Chemical Constituent of Alpinia purpurata Hydrosol Extracted by Hydro Distillation Method - Sivem, Shamalah; Mohd Aizudin, Abd Aziz; Muhammad Auni, Hairunnaja; Norasiha, Hamid (UCYP Press, 2022)
Alpinia purpurata (Halia Bara) is a perennial herbaceous plant with virtually identical qualities to common ginger, but with smaller and more pungent rhizomes. It is widely known for ornamental purposes and is also applied in the medicinal field. Extraction of essential oil and hydrosol of Alpinia purpurata can be done through the hydro distillation method. The essential oil contains α-pinene, β-caryophyllene, geranial, neral and β-pinene that contribute to medicinal values while hydrosol's chemical components are yet to be identified. Hence, the primary objective of this study is to use the hydro distillation method to identify the chemical constituents and functional groups of active chemical compounds present in Alpinia purpurata's rhizomes hydrosol. Hydro distillation is also done at different heating temperatures and distillation times to see what influence temperature and distillation time have on the components and active compounds in the hydrosol. The powdered sample is used for extraction at 60°C, 80°C, and 100°C, with distillation periods of 1, 1.5, 2, and 2.5 hours. Burette is used to extract essential oil from the hydrosol. To further investigate the hydrosol, gas chromatography-mass spectrometry (GC-MS) and Fourier-transform Infrared Spectroscopy (FTIR) are utilised extensively. The major chemical constituents detected in Alpinia purpurata's hydrosol at 100°C for 2.5 hours of distillation time include 1-Dodecanamine (40.08 %) and functional groups present are O-H, N-H, C-H, and C=H stretching, according to GC-MS and FTIR data. The increased heating temperature and distillation time caused the denaturation of substances in the extracted hydrosol. The chemical constituents present in hydrosol are greatly different from the chemical constituents that are present in essential oil qualitatively and quantitatively.